A constituição do docente online em um contexto de educação corporativa - Casaletti, Bárbara Burgardt (2012)
This study was made in the line of research Formation, Politics and Practices in Education from the Post-Graduation Program of PUCRS and tried to clarify how is the constitution of an online professor in a context of a corporative education, out of the school limits. Its construction is based on the Resolution number 71/2010, from the Superior Board of Justice of Work CSJT, which institute the National Politic of Distance Education and Selfinstruction to the public servers from the Justice of Work as well as in the Resolutions numbers 126/2011 and 159/2012, from the National Board of Justice CNJ, that manages the National Plan of Capacity of Servers and Magistrate and Formation of Magistrates and Servers from the Judicial Power. The research has a descriptive quality nature and used recommendations from Engers (1999) to select some answers from people from investigated universe three professors and two students, some of them servers from the Judiciary Power and other no. At this time, one of the relevant aspects of the investigation was the use of the Facebook, with a video call, to make the interview with two professors, showing how the social net can also be used to academic purpose and not only social. With the collected data, it was made a textual discursive analysis as Moraes and Galiazzi (2011) to analyze the speech of the interviewee. From this analysis, three categories came up to explain the constitution of online instructor. The first of them, Online instructor features, came with four deployments: promote the interactive; dominate the knowledge of the professional specialty; know the technologic resources and be virtual present. The second, Instructor development wanted from the online instructor, resulting two deployments: guide the pedagogic process and act as mediator in the relation from the student and the knowledge. The last category, Didacticpedagogic references that substantiates the practice of an online instructor, pointed as deployments: the pedagogy of parangolé ; the pedagogy centered in the relation student, professor and goal of knowledge and theory principals of Vygotsky and Piaget